1986
DOI: 10.1002/apmc.1986.051380108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of addition of sepiolite on the mechanical properties of glass fiber reinforced polypropylene

Abstract: Short glass fiber reinforced polypropylene is one of the composites with the widest range of applications in the plastics industry. The partial replacement of the glass fibers by sepiolite, brings forth a hybrid composite with better mechanical properties and, as a result, enhanced compatibility and better interfacial adhesion as a consequence of the surface properties of the sepiolite. The results obtained are also interesting from a practical point of view, as they allow for considerable reductions in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The physical and mechanical characteristics can further be modified by adding a solid filler phase to the matrix body during the composite preparation. It has been observed that by incorporating filler particles into fiber-reinforced composites, synergistic effects can be achieved in the form of higher modulus and reduced material cost, yet accompanied with decreased strength and impact toughness (Acosta, et al 1986;Pukanszky, 1995). Gracia, et al (1987Gracia, et al ( , 1983 suggested this kind of multi-phase composite technique to improve the matrix-dominated properties of continuous fiber-reinforced composites.…”
Section: Introductionmentioning
confidence: 97%
“…The physical and mechanical characteristics can further be modified by adding a solid filler phase to the matrix body during the composite preparation. It has been observed that by incorporating filler particles into fiber-reinforced composites, synergistic effects can be achieved in the form of higher modulus and reduced material cost, yet accompanied with decreased strength and impact toughness (Acosta, et al 1986;Pukanszky, 1995). Gracia, et al (1987Gracia, et al ( , 1983 suggested this kind of multi-phase composite technique to improve the matrix-dominated properties of continuous fiber-reinforced composites.…”
Section: Introductionmentioning
confidence: 97%
“…The inclusion of such particulate fillers into polymers is primarily targeted at cost saving and improvement in specific properties . Synergistic effects of higher modulus and reduced material cost are observed by incorporating hard filler particles into polymers . Fly ash is one such filler, which is a waste by‐product derived from thermal power plants .…”
Section: Introductionmentioning
confidence: 99%
“…Being light-weight, they are the most suitable materials for weight sensitive applications, but their high cost becomes a limiting factor for commercial applications. However, it has been observed that by incorporating filler particles into the fiber reinforced composites the performance of composites can be improved [6][7][8][9][10][11][12]. Cement By-Pass Dust (CBPD) is a by-product of cement manufacturing.…”
Section: Introductionmentioning
confidence: 99%